Specificity testing by point prevalence as a simple assessment strategy using the Roche Elecsys anti-SARS-CoV-2 immunoassay - Kittel, Maximilian; Findeisen, Peter; Muth, Maria-Christina; Thiaucourt, Margot; Gerhards, Catharina; Neumaier, Michael; Haselmann, Verena (International journal of infectious diseases, 2021)
Background - The detection of antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is mandatory for the diagnosis, retrospective assessment of disease progression, and correct evaluation of the current infection situation in the population. Many such assays have been launched by various manufacturers. Unfortunately, the new US Food and Drug Administration emergency use regulations have resulted in a situation where laboratories have to perform their own validation studies but many of these laboratories do not have the biobank needed to conduct the studies. - Methods - We introduce a method that allows institutions to quickly perform a verification study in a low-prevalence infection situation. As proof of concept, we used the Roche Elecsys® anti-SARS-CoV-2 electrochemiluminescence immunoassay and an SAP-based hospital information system. The Shenzhen YHLO Biotech IgM and IgG assay targeting other surface patterns was used as a confirmatory test. - Results - The Roche assay demonstrated a limit of detection of 0.069 cutoff index and successfully passed the performance validation according to Clinical and Laboratory Standards Institute EP15-A3. The study population of 627 inpatients has a median age of 64 years, and approximately 13% of the group were under intensive care at the respective time point. All patients included tested negative for SARS-CoV-2 infection by quantitative reverse transcription polymerase chain reaction (cobas® 6800, Roche, Mannheim, Germany). Only one false-positive result was obtained, resulting in a specificity for the Roche Elecsys anti-SARS-CoV-2 test of 99.84% and a negative predictive value of 99.98%. - Conclusions - The anonymized use of residual material enables quick evaluation of anti-SARS-CoV-2 immunoassays, as shown in this work with the Roche Elecsys assay. Comparison of the control population with economic data makes it possible to validate the sampling set and therefore to determine diagnostic specificity. By use of the approach chosen, it was shown that the Roche test achieved very good results in terms of diagnostic specificity, reproducibility, and limit of detection.
Gesehen am 28.07.2021